2004
DOI: 10.1530/eje.0.1500065
|View full text |Cite
|
Sign up to set email alerts
|

Association of endogenous testosterone with blood pressure and left ventricular mass in men. The Tromso Study

Abstract: Objective: To test the hypothesis that lower endogenous testosterone levels are associated with higher blood pressure, left ventricular mass, and left ventricular hypertrophy. Design: Population-based cross-sectional study. Methods: Sex hormone levels, measured by immunoassay, anthropometric measurements and resting blood pressure were studied in 1548 men aged 25-84 years; echocardiography was completed in 1264 of these men. Partial correlations and multiple regressions were used to estimate the associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
192
2
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(221 citation statements)
references
References 38 publications
16
192
2
11
Order By: Relevance
“…A negative correlation between testosterone and blood pressure has been demonstrated in elderly men 37,38) . Some studies have reported that the serum testosterone level is an independent negative predictor for the development of arterial stiffness 39,40) and testosterone replacement therapy has been shown to improve arterial stiffness in hypogonadal men 41) .…”
Section: Androgens Are Associated With Arterial Diseases In Humansmentioning
confidence: 97%
“…A negative correlation between testosterone and blood pressure has been demonstrated in elderly men 37,38) . Some studies have reported that the serum testosterone level is an independent negative predictor for the development of arterial stiffness 39,40) and testosterone replacement therapy has been shown to improve arterial stiffness in hypogonadal men 41) .…”
Section: Androgens Are Associated With Arterial Diseases In Humansmentioning
confidence: 97%
“…Although there are many unanswered questions regarding the mechanism by which testosterone may affect the process of atherosclerosis and risk of death, one proposed mechanism is that testosterone acts through modulation of classical cardiovascular risk factors, supported by findings of a favourable relationship with HDL-cholesterol (21), blood pressure and ventricular mass (22), waist circumference (23), and HbA1c (24). Furthermore, testosterone supplementation of hypogonadal men shifts cytokine balance towards less inflammation (25), which plays a key pathophysiological role in plaque formation.…”
Section: Events (N)mentioning
confidence: 99%
“…The majority of men in the youngest group studied (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) were single compared to the rest of the older groups. Contrariwise, the majority of men in the oldest group (48+) were married, compared to the youngest group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Furthermore, while the youngest group had similar numbers of men with and without dependents, the majority of men in the older groups had dependents; further statistical testing was limited because of the sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Low testosterone levels have been associated with, stress, injury, chronic diseases like diabetes, hypertension and cancer. 6,18 Symptoms associated with low testosterone levels include depression, fatigue, irritability, reduced libido, body pains, and decreased sexual performance.…”
mentioning
confidence: 99%